The Mortal Instruments: City of Glass - Book 3 - Clare, Cassandra (New York : Margaret K. McElderry Books, 2009)
Clary, who is still seeking a cure for her mother's enchantment, travels to get the City of Glass, the capital of the forbidden country of the secretive Shadowhunters, where she uncovers important truths about her family's past.
Keywords: Supernatural -- Fiction; Demonology -- Fiction; Magic -- Fiction; Vampires -- Fiction; New York (N.Y.) -- Fiction